Cannabis Expectancies for Sleep. Issue 5 (20th October 2019) - Altman, Brianna R.; Mian, M.N.; Slavin, M.; Earleywine, M.
ABSTRACT: Up to 35% of adults in the United States suffer from sleep disturbances, which covary with a host of negative mental and physical health outcomes. Previous research suggests that cannabis' sedative effects may be associated with improved sleep. The present study examined the self-reported effect of cannabis use on individual's sleep-related problems. Participants included 311 individuals recruited online, who reported both sleep-related problems and cannabis use. Analyses revealed that participants expected cannabis to decrease the incidence of sleep-related problems, including allowing participants to have an earlier bedtime, to fall asleep more quickly, and to have a longer night's sleep. Moreover, expectancies about the influence of cannabis on sleep negatively covaried with cannabis-related problems. These findings suggest that individuals believe using cannabis might positively influence their sleep quality and believing so may be protective against cannabis problems. Randomized control trials of cannabis for insomnia appear justified.